Does Green Supply Chain Management Influence to Suppliers’ Performance? Mediating Role of Social Capital - Aimi Zulhazmi Abdul Rashid; Adel Ali Yassin Alzyoud; Fayez Hamed Abdo Al Shdaifat; Khairi Mohamed Omar (International Journal of Supply Chain Management, 2019)
Present study is ascertain to elaborate the role of green supply chain management towards the suppliers’ performance. Further, the role of social capital as a potential mediator is also explored in the Thai business to business (B2B) context. Data was collected by using the survey questionnaires. Different statistical tests for measurement model and hypothesis testing respectively. Findings highlighted that suppliers’ performance both in environmental and operational terms improves due to the GSCM practices. Furthermore, it also appeared to be the major interpreter for the social capital (rationale and structural). In addition, results also supported the multidimensional impact of social capital on suppliers’ performance. Lastly, both dimensions of the social capital proved to be significant mediator for the relationship between green supply chain management practices and suppliers’ performance. This study comes with the valuable insights to develop understanding about the key role of green supply chain practice and social capital to enhance the suppliers’ performance.